AKIBAT HUKUM TERHADAP PARA PIHAK DALAM PENYELESAIAN KREDIT BERMASALAH MELALUI RESTRUKTURISASI KREDIT PADA BANK CIMB NIAGA - EDDY SAPUTRA (PREMISE LAW JURNAL, 2016)
Credit restructuring is an alternative which is done by many banks, including recapitalized ones. The measures taken by Bank Indonesia to help credit restructuring process is by publishing the Decree of Directors of Bank Indonesia No. 31/150/KEP/DIR on November 12, 1998 on Credit Restructuring and the establishment of Satgas (Special Unit) of Credit Restructuring. The research used judicial normative and descriptive analytic methods. The result of the research shows that nonperforming loan can be restructured in Bank CIMB Niaga, Medan Branch when debtors have problems (business setback/serious financial problem) so that they fail to pay off the principal plus interest, on condition that they have good business prospect and are expected to be able to pay off the debt after the credit restructuring. Legal consequences against debtors are that there is the change of agreement between the Bank as creditor and the debtors in the right and obligation of both parties in the credit restructuring and the revocation of initial loan agreement which has been agreed and changed to new agreements which are indicated by the signing of new loan agreement as the result of new credit restructuring. Keywords: Nonperforming Loan, Credit Restructuring, Bank CIMB Niaga Medan Branch